TOURISM AND ECONOMIC GROWTH MODERATED BY FOREIGN DIRECT INVESTMENT AND EXCHANGE RATE IN SELECTED AFRICAN ECONOMIES. - Okwo, Glory; Awogbemi, Titus Olufemi; Egbon, Peter Chukwuyem (International Journal of Allied Sciences (IJAS), 2024)
This study used panel data from 1995 to 2022 for seven African countries (Nigeria, Tunisia, Kenya, Tanzania, South Africa, Morocco, and Mauritius) and the vector autoregressive (VAR) technique to examine the relationship between tourism and economic growth moderated by foreign direct investment and exchange rate. The variables for the study are tourism receipts (TR), tourist arrivals (TAR), exchange rate (EXR), foreign direct investment (FDI), and GDP as a proxy for economic growth. Findings from the study revealed that tourism receipts of the selected countries at various lags had a positive and non-significant effect on the economies in the short-run. In contrast, tourism receipts at various lags positively and significantly impacted the countries' economic growth in the long- run. Tourist arrivals at various lags reveal a negative and non-significant effect on economic growth in the short-run, while in the long-run, tourist arrivals at various lags had a positive and significant impact on the growth of the economies. The moderating effect of exchange rate and foreign direct investment on tourism were positive and significant both in the short and long run. while in the long-run period, tourism receipts at various lags had a positive and significant effect on economic growth of the countries. Tourist arrivals at various lags reveal a negative and non-significant effect on economic growth in the short-run, while in the long-run period, tourist arrivals at various lags had a positive and significant impact on the growth of the economies. The moderating effect of exchange rate and foreign direct investment on tourism were positive and significant both in the short and long-run. The study recommended that African leaders work together to coordinate policy initiatives to maximize the potential of tourism on the continent to combat unemployment and poverty and promote sustainable growth